Astroglial networks in health and disease: New Frontiers - Verkhratsky, Alexei (Italian Journal of Anatomy and Embryology, 2015)
The common and prevailing point of view considers neurones as main substrates of pathological progression of neurological diseases. Today, however, we know that integration and information processing in the brain occurs though close interactions of two cellular circuits represented by neuronal networks embedded into internally connected astroglial syncytia. Our understanding of glial function changed dramati- cally over last two decades. This change concerns the whole concept of how the brain is organized, and how the development, life and death of neural circuits are controlled. There is compelling evidence demonstrating that these are the astrocytes that are creating the compartmentalisation in the CNS, and these are the astrocytes that are able to integrate neurones, synapses, and brain capillaries into individual and relatively independent units. Astroglial syncytia allow intercellular communica- tion routes, which permit translocation of ions, metabolic factors and second messen- gers. The resulting potential for parallel processing and integration is significant and might easily be larger, but also fuzzier, than the binary coded electrical communica- tion within the neuronal networks. The neuronal-glial circuitry endowed with distinct signalling cascades, form a “diffuse nervous net” suggested by Golgi, where millions of synapses belonging to very different neurones are integrated first into neuronal- glial-vascular units and then into more complex structures connected through glial syncytia. These many levels of integration, both morphological and functional, pre- sented by neuronal-glial circuitry ensure the spatial and temporal multiplication of brain cognitive power. Neuroglial cells are intimately involved in all forms of neurological diseases and this are neuroglia, which, to a very large extent, determine the progression and outcome of neuropathological process. Astrocytes are specifically involved in vari- ous neurodegenerative diseases including Alzheimer’s disease, Amyotrophic lateral sclerosis, Parkinson’s disease and various forms of dementia. Recent evidence sug- gest that early stages of neurodegenerative processes are associated with atrophy of astroglia, which causes disruptions in synaptic connectivity, disbalance in neurotrans- mitter homeostasis and neuronal death through increased excitotoxicity. At the later stages astrocytes became activated and contribute to neuro-inflammatory component of neurodegeneration.